VISUALIZATION, MODELING, AND GRAPHICS FOR ENGINEERING DESIGN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The process engineering design (design) begins with visualization, i.e., reviewing the problem and possible solutions. Then, sketching leads to the preparation of the initial idea. Next step is preparation of geometric models, which are used for a variety of engineering analysis and, finally, creating detailed drawings and/or 3D models, which are used for the production process. Visualization, sketching, modelling and preparation of technical documentation are ways in which engineers and technologists communicate in creating new products and structures in the modern technical world.